Analisis Sistem Antrian Online Kunjungan Pasien Rawat Jalan Terhadap Database System Pada Rumah Sakit Ananda Bekasi Berbasis Web - Endah Prawesti Ningrum; Indah Rizki Maulia; Ahmad Muchlisin Natas Pasaribu (Jurnal Kajian Ilmiah, 2026)
This study aims to identify the strengths and weaknesses of the web-based online queue system for outpatient visits at Ananda Hospital Bekasi. This research employs the waterfall method, which is an information system development model that is systematic and sequential. Data collection was conducted through observation and interviews, and the results were analyzed in depth. The findings indicate that the information system implemented at Ananda Hospital Bekasi has certain strengths and weaknesses. The system is capable of reducing patient waiting time and alleviating queue congestion. However, there are still several aspects that need improvement, such as ensuring the accuracy of patient data and enhancing patient awareness about the online queue system, which can facilitate the service process at Ananda Hospital Bekasi